Late Surgical Bleeding Following Total Artificial Heart Implantation. Issue 10 (19th August 2015) - Hermsen, Joshua L.; Smith, Jason W.; Pal, Jay D.; Mahr, Claudius; Masri, S. Carolina; Dardas, Todd F.; Cheng, Richard K.; Mokadam, Nahush A.
Abstract Introduction Mechanical circulatory support for heart failure, including the Total Artificial Heart (TAH, Syncardia, Tucson, AZ, USA) has increased in recent years. This report describes bleeding complications associated with the device. Methods A single institution prospectively maintained quality improvement database was reviewed encompassing the first year of clinical experience with the TAH. Patients who underwent TAH implantation were identified, and a review of complications and outcomes was undertaken. Results Ten patients underwent TAH implant. Four patients experienced delayed postoperative bleeding. In three patients the manifestation of bleeding was tamponade and evidenced by TAH decreased cardiac output. In two patients, at postoperative days 31 and 137, there was a partial disruption of the aortic anastomosis along the outer curvature with pseudoaneurysm formation. Both were repaired by primary suture closure, without use of cardiopulmonary bypass. There was no mortality attributable to bleeding. Conclusions TAH patients are at risk for delayed postoperative bleeding, often manifest as an acute decrease in cardiac output. Due to pulsatility and high dP/dT, bleeding from the aortic anastomosis should be considered in the differential of a patient with low flow and/or tamponade. doi: 10.1111/jocs.12601 (J Card Surg 2015;30:771–774)